PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN PURWOSASONO DAN DUSUN BABADAN BELUK DESA KECAMATAN BAYAT PROVINSI JAWA TENGAH KABUPATEN KLATEN - , WAHUD AMINULLOH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final task is explains about measurement and mapping process that produces spatial data information from the earth's surface. Spatial data is data generated planimetric and elevation data presented in map form. The method used is map-making map control framework which includes the measurement framework of horizontal control, vertical control framework, the measurement of planimetric detail and the high point and digital representations. The result is a large-scale situation map 1: 500 were present spatial data on the earth's surface and Hamlet Hamlet Purwosasono Kurt, Village outs, District Bayat, Klaten, Central Java by using the projection system UTM (Universal Transverse Mercator).